Effect of vitaliquid multivitamin addition and cassava leaf flour to feed on the growth and survival of saline tilapia fry (Oreochromis niloticus) - Wahyu, Inge Eka Nur; Nuhman, Nuhman (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Saline tilapia (Oreochromis niloticus) is a fish that is relatively easy to maintain in fresh or brackish water conditions. Adding cassava leaf meal and multivitamin vitaliquid to the feed can increase the high appetite of fish and accelerate the growth of saline tilapia. This research was implemented to find the effectiveness of multivitamin vitaliquid on the growth and survival rate of saline tilapia (Oreochromis niloticus). The rule used is an experiment with a Completely Randomized Design (CRD), four treatments and six replications. Data showed that the largest absolute weight growth was achieved by P4 of 4.98 ± 3.14 grams, while the smallest result was at P1 which was 2.78 ± 0.21 grams. The greatest absolute length growth was achieved at P3 resulting in a length of 2.3 ± 0.86 cm, while the smallest result was at P1 which was 1.3 ± 0.41. The highest specific growth rate was achieved at P3 11.35 ± 0.57%, while the lowest was at P2 of 9.53 ± 1.58%. The highest survival rate of saline tilapia was found in P1 at 95%, while the lowest was found in P3 and P4 which had no different results, 81.7%. The effectiveness of multivitamin vitaliquid in commercial feed given cassava leaf flour in terms of absolute weight growth, absolute length growth, specific growth rate and survival of saline tilapia fry is very effective compared to just being given pellet feed.